Crossing the river while feeling the rocks: Incremental land reform and its impact on rural welfare in China - Bruce, John W.; Li, Zongmin (International Food Policy Research Institute, 2009)
Between 1978 and 1984, a massive shift from collective to household agricultural production took place in China. These incremental reforms, which Deng Xiaoping called "crossing the river while feeling the rocks," eventually gave 95 percent-160 million rural Chinese families-the right to oversee household plots, leading to stunning gains in productivity.1 Despite the success of the HRS, the enhancement of property rights is an ongoing reform process. Landholders depended on tenure agreements that could be changed at any time. Rural areas did not have the same right to profit from appreciating land values as urban landholders. As cities have expanded rapidly, municipalities have requisitioned rural land and issued it to new users at urban prices much higher than that paid to the rural villages. The policy debate about the appropriate pace for strengthening rural land use rights continues. This reform, the Household Responsibility System (HRS), provided strong incentives for farmers to increase labor and improve land, since they could profit from any marketable surplus they produced. Meanwhile, the state set quotas and purchased crops, providing reliable markets for increased production. It also strongly supported farmers by managing irrigation and the agricultural extension system. The state's earlier investments in rural nonfarm infrastructure paid off under the reforms, as workers released from agriculture by the more efficient use of labor found employment in local rural industries. In the years following the property reforms, the quality of life in rural China improved dramatically: per capita rural income more than doubled from 1978 to 1984. Having examined the substance, process, and effects of the reforms, this paper asks what lessons from the reforms are relevant for other developing countries. In spite of differences among countries, some elements of the Chinese reform experience seem highly relevant to others engaged in the struggle to develop.